Virtual screening for ganodermal polyketide synthases inhibitor - Ong, Chia Sui; Ke, Hwi Mei; Wong, Mui Yun (Institute of Plantation Studies, Universiti Putra Malaysia, 2017)
Polyketide synthases (PKSs) is a huge family of multifunctional enzymes that produce secondary metabolites, known as polyketides, which can be found in different organisms such as fungi, bacteria and plants. Fungal polyketides (PKs) have been reported as essential virulence factors in plant-pathogen interactions. The main purpose of this project is to use in silico virtual screening technique to discover potential inhibitors that can have considerable interactions with the target PKS protein. The PKS gene sequence was identified from the genome library of Ganoderma. The ketosynthase (KS) domain of the PKS protein was taken for structural prediction by homology modelling. The model predicted was then docked against a library of compound in ZINC database for interaction analysis. In consideration of chemical and toxicity properties of ligands found to interact with the target KS domain, two ligands were shortlisted, namely tomatidine and posaconazole. Further verification on the effect of these ligands towards PKS activity will be conducted in future studies.